On the lower estimate of the distortion of distance for one class of mappings - Markish, A. A.; Salimov, R. R.; Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We study the behavior of one class of mappings with finite distortion in a neighborhood of the origin. Under certain conditions imposed on the characteristic of quasiconformality, we establish a lower estimate for the distortion of distance under mappings of the indicated kind.